USE OF REMOTE SENSING TECHNOLOGIES IN MAPPING OF AGRICULTURAL CROP TYPES - Hamroqul Ravshanov Amirqulovich; Komil Khujakeldiyev Nosirovich; Jahongir Nosirov Komil o‘g‘li (Journals Park Publishing, 2023)
In the article, space images when compiling various maps for remote sensing, when you need to create a thematic map of a particular area, enough information can be obtained from remote sensing signals in a short period of time. This speeds up card production and improves accuracy. The use of remote sensing technologies in crop mapping greatly simplifies the mapping work.
Keywords: remote sensing, map, electronic map, monitoring, GPS device, GIS, aerial photography, cadastre maps, crop.